Pengembangan Strategi Pembelajaran Matematika Berdiferensiasi Berbasis Gaya Belajar STIFIn - Dyah Ayu Sulistyaning Cipta; Rachmawati (Universitas Insan Budi Utomo, 2025)
Differentiated instruction is a key feature of the Merdeka Curriculum, emphasizing the importance of addressing students’ individual learning needs without categorizing them into fixed groups. In practice, however, many teachers face challenges in implementing effective differentiation strategies, especially in mathematics education. This study aims to develop a differentiated mathematics instructional strategy by utilizing the STIFIn learning style approach as a responsive adaptation tool, without classifying or grouping students permanently. The research employed the 4D development model (Define, Design, Develop, Disseminate), focusing on the initial three stages: identifying instructional needs, designing the strategy, and developing learning materials. The subjects included fifth-grade elementary students and a mathematics teacher from a primary school in Central Java. Expert validation results indicated that the strategy is highly valid. Limited trials showed the strategy was practical for classroom implementation and had the potential to enhance students’ conceptual understanding and engagement in mathematics learning. The discussion reveals that this approach aligns with the principles of Universal Design for Learning (UDL) and remains inclusive. The strategy enables teachers to respond to student diversity through STIFIn-based cognitive tendencies without compromising flexibility. These findings offer both theoretical and practical contributions to the development of more adaptive, personalized, and student-centered mathematics instruction.